Electrochemical Determination of Tyrosine using a Novel Tyrosinase Multi-Walled Carbon Nanotube (MWCNT) Polysulfone Modified Glassy Carbon Electrode (GCE). (22nd January 2020) - Phelane, Lisebo; Gouveia-Caridade, Carla; Barsan, Madalina M.; Baker, Priscilla G. L.; Brett, Christopher M. A.; Iwuoha, Emmanuel I.
Abstract: The modification of polysulfone (PSF) with multi-walled carbon nanotubes (MWCNT) is presented as a platform for the development of a tyrosinase biosensor. PSF, dissolved in dichloromethane, was deposited on a glassy carbon electrode (GCE), after which MWCNT functionalized in nitric acid, was drop coated on the PSF layer. Tyrosinase enzyme (TyOx), crosslinked with glutaraldehyde, was subsequently deposited on the MWCNT/PSF/GCE transducer to constitute the tyrosinase biosensor. The MWCNT/PSF/GCE (sensor) and TyOx/MWCNT/PSF/GCE (biosensor) were characterized using cyclic voltammetry and electrochemical impedance spectroscopy. Scanning electron microscopy was used to study the morphological changes after each modification step. Cyclic voltammetry measurements confirmed that MWCNT/PSF/GCE was a better platform for the direct detection of tyrosine than MWCNT/GCE or PSF/GCE. A well-defined analytical peak at 0.79 V with respect to Ag/AgCl was observed that was clearly distinguishable from the background current. The tyrosinase biosensor showed a very low limit of detection (0.3 nM) and a very high sensitivity (1.988 µA µM −1  cm −2 ) towards tyrosine detection compared to comparable devices reported in the literature.